Integrated Marketing Communication [IMC] Desa Wisata Wonolopo Dalam Upaya Publikasi Ikonik “Kampoeng Jamu” - Imam Husni Al Amin; Edy Winarno; Budi Hartono; Dwi Budi Santoso (IKRA-ITH ABDIMAS, 2023)
Awareness for the community in the tourism that the area is one of the tourist destinationsthat has the potential to improve the people's economy, so the pioneers and movers of the touristvillage must be able to synergize all existing components to move together to build their villageand participate in every activity that exists during tourist visits. Management that is conditionedand managed by the community itself, so that young people who will later become pioneers andmovers are equipped with the ability to publish and promote their tourist villages by utilizinginformation technology, especially digital marketing. Optimizing the use of information technology in the form of digital marketing as a meansto promote and publicize Kampoeng Jamu, Wonolopo sub-district for young people driving theWonolopo tourist village to be very strategic in relation to the acceleration to be able to lift thepotential that exists in the area so that the tourism potential in the Wonolopo tourist village oneof them which is an icon of the Wolopo tourist village is "kampoeng Jamu" with traditionalherbal products carried so that it is more widely known. Integration of MarketingCommunication is provided in digital marketing materials with digital content in the form ofphotos of products and services as well as story telling so that they are very familiar toconsumers, followed by material on optimal use of social media that can be made viral byeveryone involved in digital marketing for tourist villages. Wonolopo, specifically forcommodities from Kampoeng Jamu